CUL5–ASB6 Complex Promotes p62/SQSTM1 Ubiquitination and Degradation to Regulate Cell Proliferation and Autophagy - Gong, Liyan; Wang, Kaihua; Wang, Mengcheng; Hu, Ronggui; Li, Huaguang; Gao, Daming; Lin, Moubin (Frontiers in Cell and Developmental Biology, 2021)
p62/SQSTM1 (sequestosome-1) is a key protein involved in multiple cellular bioprocesses including autophagy, nutrient sensing, cell growth, cell death, and survival. Therefore, it is implicated in human diseases such as obesity and cancer. Here, we show that the CUL5–ASB6 complex is a ubiquitin E3 ligase complex mediating p62 ubiquitination and degradation. Depletion of CUL5 or ASB6 induced p62 accumulation, and overexpression of ASB6 promoted ubiquitination and degradation of p62. Functionally, ASB6 overexpression can inhibit the proliferation of MEF and hepatocellular carcinoma cells by reducing p62 protein level, and impair the occurrence of autophagy. Overall, our study identified a new molecular mechanism regulating p62 stability, which may provide additional insights for understanding the delicate control of p62 and cell proliferation–autophagy control in physiological and pathological settings.